Respostas
respondido por:
4
x - 3 = 0
2x-y = 1
-----------
vamos isolar "x" na primeira equação e substituir na segunda.
x = 3
2*3 - y = 1
-y = -5
y = 5
S = (3,5)
5x - y = 4
2x - y = -5 *(-1)
--------------
5x - y = 4
-2x + y = 5
--------------
3x = 9
x = 3
5*3 - y = 4
15 - y = 4
-y = 4 - 15
y = 11
S = (3,11)
tá valendo?
abraço!!!
2x-y = 1
-----------
vamos isolar "x" na primeira equação e substituir na segunda.
x = 3
2*3 - y = 1
-y = -5
y = 5
S = (3,5)
5x - y = 4
2x - y = -5 *(-1)
--------------
5x - y = 4
-2x + y = 5
--------------
3x = 9
x = 3
5*3 - y = 4
15 - y = 4
-y = 4 - 15
y = 11
S = (3,11)
tá valendo?
abraço!!!
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás